Context and motive in the perpetuation of racial harassment and violence in North Staffordshire, 2004 - Jefferson, Tony (UK Data Service, 2006)
This project addressed the question of why some people engage in racially-motivated violence, and how their motivations for doing so intersect and/or conflict with publicly-expressed nationalist, racist/anti-racist, and religious sentiments. The research was conducted in North Staffordshire, and drew on documentary evidence, in-depth interviews with perpetrators and other individuals, and focus groups conducted with members of the local community. The research found that industrial decline had led to many people in North Staffordshire feeling a sense of loss, in that a whole way of life had gone, never to return. Very many white residents saw the presence of migrant and minority ethnic populations as an emblem of the local area's decline, and an uncomfortable reminder of their inability to secure decent lives for themselves and their families. Some of the most disadvantaged and vulnerable people were trying to cope with their feelings of shame, envy and disgust by projecting them often aggressively, sometimes violently onto migrant and minority ethnic groups and individuals.